The relationship between profiles and transitions of internalizing and externalizing symptoms in children and suicidal thoughts in early adolescence. Issue 15 (2nd November 2020) - Johnson, Dylan; McLennan, John D.; Heron, Jon; Colman, Ian
Abstract: Background: Adolescence is a high-risk period for the onset of suicidal thoughts and behaviors. Identification of preceding patterns of internalizing and externalizing symptoms that are associated with subsequent suicidal thoughts may offer a better understanding of how to prevent adolescent suicide. Methods: Data from the National Longitudinal Survey of Children and Youth, a prospective population-based Canadian cohort, contained Child Behavior Checklist items which were used to examine profiles and transitions of internalizing and externalizing symptoms in children, aged 6–11 years ( n = 8266). The association between these profiles/transitions and suicidal thoughts in adolescents was examined using multivariate logistic regression modeling. Results: Latent profile analyses identified four measurement invariant profiles of internalizing and externalizing symptoms at ages 6/7 and 10/11: (1) low on all symptoms, (2) moderate on all symptoms, (3) high on all symptoms, and (4) high on hyperactivity/inattention and internalizing. Recurrent (homotypic or heterotypic) and increasing symptoms from 6/7 to 10/11 were associated with suicidal thoughts in adolescence, compared to those with stable low symptoms. Those with decreasing symptoms from 6/7 to 10/11 were not at increased risk of suicidal thought in adolescence. Conclusions: While patterns of recurrent symptoms were associated with suicidal thoughts, a similar association was observed between profiles at age 10/11 years and suicidal thoughts. This suggests that the recent assessments of mental health symptoms in children may be as sufficient a predictor of adolescent suicidal thought as transition profiles.